Constituents of two Flourensia species - Uriburu, María L. (2004)
The MeOH extract of aerial parts of Flourensia riparia Grisebach (Asteraceae) afforded a sesquiterpene lactone, 4beta-hydroxy-4,10alpha-dimethyl-7alphaH,8alphaH-eudesman-11-ene-8,12-olide, together with septuplinolide, its isomer at positions C-5 and C-10. In addition, known flavonoids, p-hydroxyacetophenone derivatives, carabrone and isoalantolactone were identified. Three known flavonoids and a benzofuran were isolated from Flourensia campestris Wedd.